Meta-Analysis the Effect of Exclusive Breastfeeding on Anemia in Children Under Five - Azizah, Fikri Dian Dinu; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: The prevalence of iron deficiency anemia is still high, especially in children under five. One effort to prevent iron deficiency anemia is exclusive breastfeeding for newborns. This study aims to analyze exclusive breastfeeding on the incidence of anemia in children under five. Subjects and Method: This study is a systematic review and meta-analysis, with PICO as follows: Population= toddlers aged <5 years; Intervention= exclusive breastfeeding; Comparison= non-exclusive breastfeeding; Outcome= iron deficiency anemia. The articles used in this study were obtained from several databases including PubMed, Springer Link, Science Direct, and Google Scholar, which were published from 2012 to 2022. The keywords to search for articles are as follows: